Design and conduct of non-inferiority trials - Durkalski-Mauldin, Valerie (Henry Stewart Talks, 2018)
When is ‘non-inferiority’ the correct question for your trial, Selection of an acceptable margin of non-inferiority, Selection of the control arm (placebo/active/both), How to interpret the study results